2018
DOI: 10.1016/j.cels.2018.10.013
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Parameter Estimation Enables the Prediction of Drug Response Using a Mechanistic Pan-Cancer Pathway Model

Abstract: Highlights d Detailed, large-scale mechanistic model of cancer-related signaling pathways d Speedup of over 10,000-fold enables data-driven modeling at unprecedented scales d Pronounced parameter uncertainties do not imply pronounced prediction uncertainties d Mechanistic models can predict response to drug combinations from single drug data

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
173
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 126 publications
(185 citation statements)
references
References 82 publications
(103 reference statements)
0
173
0
1
Order By: Relevance
“…In Loos et al (2018), hierarchical optimization was performed using objective gradients computed via forward sensitivity analysis. However, for large-scale models adjoint sensitivity analysis has shown to be orders of magnitude faster (Fröhlich et al, 2018), because essentially here the evaluation of state sensitivities is circumvented by defining an adjoint state p ∈ R nx which does not scale in the number of parameters (Fröhlich et al, 2017b).…”
Section: Combining Hierarchical Optimization and Adjoint Sensitivity mentioning
confidence: 99%
See 4 more Smart Citations
“…In Loos et al (2018), hierarchical optimization was performed using objective gradients computed via forward sensitivity analysis. However, for large-scale models adjoint sensitivity analysis has shown to be orders of magnitude faster (Fröhlich et al, 2018), because essentially here the evaluation of state sensitivities is circumvented by defining an adjoint state p ∈ R nx which does not scale in the number of parameters (Fröhlich et al, 2017b).…”
Section: Combining Hierarchical Optimization and Adjoint Sensitivity mentioning
confidence: 99%
“…Applications range from the description of signaling pathways (Klipp et al, 2005) to the prediction of drug responses (Hass et al, 2017) and patient survival (Fey et al, 2015). With the availability of scalable computational methods and increasing computing power, larger and larger models have been developed to capture the intricacies of biological regulatory networks more accurately (Bouhaddou et al, 2018;Fröhlich et al, 2018). In Fröhlich et al (2018), we demonstrated how such a large-scale mechanistic model integrating various cancer-related signaling pathways is able to, e.g., predict the response of cancer cells to drug combinations based on measurements for single treatment responses, a task which is commonly not possible with statistical models.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations